Oil producing communities' initiatives and the dynamics of conflict and peace building in Niger Delta (2012)
Local initiatives in the dynamics of conflict and peacebuilding are germane in understanding the actions and inactions of a people towards their plights and sustainable development. This study therefore adopts a qualitative methodology in investigating local communities’ initiative in the unending conflicts and peacebuilding processes in Nigeria, using Gokana, Onelga, and Etche communities in Rivers State as case study. Major findings revealed that the roles and networks of key indigenous institutions such as elder’s council, ruling houses, mothers of the land, traditional healers and witch-doctors were vital in directing the affairs of the communities. However, they were often sidelined by government and the multinational corporations. This reality has continuously hindered the development of the region. Similarly, the use of technocrats, educated elites and the relative neglect of local leaders in negotiating peace were discovered as a missing link in the quest for peace and sustainable development in the region. Lastly, the study recommends that peacebuilding and development initiatives should take a bottom-top approach and be devoid of politics for a realistic sustainable development.